Penggunaan Media Pembelajaran Dalam Meningkatkan Motivasi Belajar Siswa Di Mi Mathla’ul Anwar Kab. Hulu Sungai Utara - Habib Alwi Jamalulel (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2020)
This study aims to analyze the activities of teachers at Mi Mathla'ul Anwar Kab. Hulu Sungai Utara in using learning media and the types of learning media that have been used and how the role of learning media in increasing student motivation. As many as 80% of students are actively involved in their class. This can be seen from the variety of instructional media used by teachers proven to be very effective in making students actively involved in learning. The more concrete students learn learning materials for example through hands-on experience, the easier it is for children to understand learning because they are actively involved in the process. Therefore, the use of instructional media becomes very important in clarifying the presentation of the message given by the teacher so that it can increase student motivation and learning achievement.